Verified Software. Theories, Tools, and Experiments 8th International Conference, VSTTE 2016, Toronto, ON, Canada, July 17-18, 2016, Revised Selected Papers - Blazy, Sandrine; Chechik, Marsha (Programming and Software Engineering,, 2016)
This volume constitutes the thoroughly refereed post-conference proceedings of the 8th International Conference on Verified Software: Theories, Tools and Experiments, VSTTE 2016, held in July 2016 in Toronto, ON, Canada. The 8 full papers together with 4 short papers and 5 invited papers presented were carefully revised and selected 21 submissions. The goal of the VSTTE conference is to advance the state of the art through the interaction of theory development, tool evolution, and experimental validation.